The impact of organizational commitment on professional development among faculty at private undergraduate universities in Yunnan, China - Fan, Jiaqi; Chang, Yuan-Cheng (Edelweiss Applied Science and Technology, 2025)
In recent years, China's higher education community has increasingly focused on the Professional Development (PD) of faculty in private undergraduate universities. Guided by Social Exchange Theory, this study aimed to examine the impact of Organizational Commitment (OC) on teachers’ PD, with a particular focus on the mediating role of Occupational Well-Being (OWB) in this relationship. A total of 801 valid questionnaires were collected through a questionnaire survey of teachers in four private undergraduate universities in Yunnan Province, and a structural equation modeling (SEM) was utilized to test the proposed hypotheses. The results confirmed that teachers’ OC significantly improved their PD (β = .253; 95% CI: .163 - .345; p < .001), and OWB partially mediated this relationship (β = .038; 95% CI: .019 - .067; p < .001). The findings suggest that enhancing teachers’ OC is crucial to promoting their PD, with special attention paid to the key mediating role of OWB.